Two new species of Helobdella Blanchard 1896 (Hirudinida: Rhynchobdellida: Glossiphoniidae) from Taiwan, with a checklist of hirudinea fauna of the island - Lai, Yi-Te; Chang, Chih-Han; Chen, Jiun-Hong (Zootaxa, 2009)
In this study, two new species of Helobdella leeches, Helobdella octatestisaca n. sp. and Helobdella melananus n. sp., and a newly recorded species, Helobdella europaea, are reported. Morphological characters and DNA barcode analysis were used to identify the three new species. The differences between these species and other morphologically congeneric species were also compared. In addition, the potential ecological impact of these species was discussed and a checklist of the hirudinea fauna in Taiwan, including eight species in Family Glossiphoniidae, four in Hirudinidae, two in Haemopidae, two in Haemadipsidae, and two in Salifidae, was provided.